The Haematopoietic Stem Cell Niche: New Insights into the Mechanisms Regulating Haematopoietic Stem Cell Behaviour - Andrew J. Lilly; William E. Johnson; Christopher M. Bunce (Stem Cells International)
The concept of the haematopoietic stem cell (HSC) niche was formulated by Schofield in the 1970s, as a region within the bone marrow containing functional cell types that can maintain HSC potency throughout life. Since then, ongoing research has identified numerous cell types and a plethora of signals that not only maintain HSCs, but also dictate their behaviour with respect to homeostatic requirements and exogenous stresses. It has been proposed that there are endosteal and vascular niches within the bone marrow, which are thought to regulate different HSC populations. However, recent data depicts a more complicated picture, with functional crosstalk between cells in these two regions. In this review, recent research into the endosteal/vascular cell types and signals regulating HSC behaviour are considered, together with the possibility of a single subcompartmentalised niche.